Respiration, predatory behavior and prey consumption by Podisus nigrispinus (Heteroptera: Pentatomidae) nymphs exposed to some insecticides. (December 2020) - Silva, Wiane Meloni; Martínez, Luis Carlos; Plata-Rueda, Angelica; Serrão, José Eduardo; Zanuncio, José Cola
Abstract: Podisus nigrispinus Dallas (Heteroptera: Pentatomidae) preys on insect pests in eucalyptus plantations where it can be exposed to insecticides used in pest control. The effect of insecticides on non-target natural enemies requires further study. The objective of the present study was to evaluate the side-effects of Bacillus thuringiensis ( Bt ), permethrin, tebufenozide and thiamethoxam on third instar nymphs of the predator P. nigrispinus in the laboratory. The toxicity of insecticides for this insect was determined by estimating their lethal concentrations. Podisus nigrispinus behavior after exposure to insecticides was analyzed using a video tracking system and the respiratory rate with a respirometer. Prey/nymph consumption was assessed after 24 h of starvation. The preference of P. nigrispinus nymphs, for prey treated or not with the insecticides, was evaluated in free choice tests. The insecticides Bt [LC50  = 1.10(0.83–1.46) mg mL −1 ], permethrin [LC50  = 0.25(0.17–0.34) mg mL −1 ], tebufenozide [LC50  = 5.71(4.17–7.57) mg mL −1 ] and thiamethoxam [LC50  = 0.04(0.02–0.06) mg mL −1 ] are toxic to P. nigrispinus nymphs. Bt and the insecticides tebufenozide, permethrin and thiamethoxam reduced the respiratory rate of P. nigrispinus . The insecticides permethrin, tebufenozide and thiamethoxam affect the locomotion of this insect's nymphs. Prey treated with Bt, permethrin and thiamethoxam are less preferred by P. nigrispinus . The survival of the nymphs of this predator was 93.3%, 66.7%, 56.6%, 0% and 0% in the control, tebufenozide, Bt, permethrin and thiamethoxam treatments, respectively. In addition, the reduction of prey consumption, treated with neurotoxic insecticides, reduces the predatory potential of this natural enemy. Bt and tefubenozide present low toxicity for P. nigrispinus, but the neurotoxic products have low compatibility with this natural enemy and, therefore, are not recommended, with this predator in the management of forest insect pests. Highlights: The predatory bug, Podisus nigrispinus is used to control the pest in forest systems. Effects on respiration, predation, behavior, and prey consumption caused by insecticides were evaluated in nymphs. Nymphs were affected after insecticide exposure, mainly with permethrin and thiamethoxam. Neurotoxic insecticides have low compatibility with this natural enemy and cannot be recommended in forestry.